EUROPEAN CULTURAL HERITAGE AND SKILLS DEVELOPMENT COURSE FOR ADULT LEARNERS’ SELF-DEVELOPMENT - Luka, Ineta (Journal of Education Culture and Society, 2021)
Aim. This article aims to evaluate the target course created and the development of adult learners’ 21st century skills during the course implementation in six EU countries. Concept. European Cultural Heritage and Skills Development Course is a culture-based blended-learning course created within the framework of the Erasmus+ project “Cultural Knowledge and Language Competences as a Means to Develop 21stCentury Skills” conducted in six EU countries: Croatia, Latvia, Slovenia, Romania, Poland and Czech Republic (Project No.2018-1-HR-01-KA204-047430; 2018-2021). The course content is presented in a form of a story, applying innovative methodologies and tools increasing adult learners’ cultural knowledge and ensuring the skills development. This article focusses on blended-learning in particular, and the course evaluation given by learners and teachers after the course implementation in the six partner countries as well as the development of adult learners’ 21st century skills. Results and conclusion.The results indicate a positive evaluation of the learning platform, the learning methodologies and tasks as well as a positive trend considering the development of learners’ 21st century skills, including the English language competences. Although the results varied from country to country, no extremely significant differences between the evaluation done by learners and the teachers were found, thus the course may be applicable to adult teaching/learning. Practical application.The created blended-learning course may be a viable option for developing adult learners’ 21st century skills and increasing their cultural awareness of the less known EU intangible cultural heritage. Originality.The contribution describes the difference between flipped, hybrid and blended-learning and introduces a novel approach of creating a blended-learning course for adult learners.